The Inter-American Human Rights System
XXI, 340 p. 12 illus. in color.
Keywords: This book critically examines the impact of the Inter-American Human Rights System (IAHRS). Going beyond traditional state compliance models of human rights impact, it develops a contextual understanding of how the IAHRS shapes political struggles between actors and institutions seeking to advance the realization of human rights and those who resist such social and political change. Par Engstrom is Senior Lecturer in Human Rights at the Institute of the Americas, University College, UK, and the academic coordinator of the International Network on the Inter-American Human Rights System.